Routine follow-up of native valve disease: real life data from a physiologist-led valve clinic. (8th February 2021) - Hyams, K; Balkhausen, K; Townsend, C
Abstract: Funding Acknowledgements: Type of funding sources: None. Purpose The 2014 American Heart Association (AHA) guidelines for the management of Valvular Heart Disease (VHD) suggest that patients with mild and moderate native VHD should be followed up with echocardiography at regular intervals. Following audits at our hospital in 2016, dedicated Physiologist Led Valve Clinics (PLVC) were initiated to improve guideline adherence. A conservative strategy for follow-up frequency based on AHA guidelines was chosen (3 years for mild VHD, and 1 year for moderate VHD). This audit aimed to ascertain adherence to this conservative follow-up strategy, and to assess the progression of VHD between echocardiographic assessments to inform a strategy for safe follow-up in our PLVC. Methods Our echocardiography database Cognos was searched for patients with isolated mild and moderate native VHD, seen in our PLVC between 2016-2018 and followed up between 2017-2019. Patients with severe, prosthetic, combined or significant mixed VHD were excluded. Echocardiography reports on McKesson were reviewed and the follow-up interval recorded for each patient. The severity of VHD at the index visit, and then at follow-up, was recorded to determine whether there had been a progression in VHD severity. For patients with progression, it was recorded whether they were symptomatic at follow-up or subsequently underwent valvular intervention. Results 466 index echocardiograms were reviewed; 134 patients were included (mean age 73.4) after removing those with exclusion criteria. The mean follow-up interval in mild VHD ranged between 587.6 ± 188.3 days, and 667.3 ± 174.6 days, well above the recommended 3 years (or 1095 days). The majority of patients with moderate VHD received follow-up well before the upper limit of AHA guidance (2 years, or 730 days). Mean follow-up ranged between 408.3 ± 80.8 days (in moderate aortic stenosis (AS)) and 504.0 ± 29.0 days (in moderate mitral stenosis (MS)). The number of patients followed up with mild VHD was very low. 1 patient in each group progressed to moderate VHD (out of 2, 3 and 5 respectively); none became symptomatic, and none progressed from mild to severe VHD. In moderate VHD, progression rates were highest in AS (34.8%). Patients with progressive disease were more frequently symptomatic (43%) or underwent valve intervention (25%). Fewer with mitral regurgitation (MR) (22%) progressed, 44.5% of whom were symptomatic, 11% undergoing intervention. Patients with moderate aortic regurgitation (AR) saw the lowest progression rates (11.4%), 50% of whom were symptomatic. There was no progression in moderate MS. Conclusions Patients with mild VHD can safely be followed up less conservatively in the PLVC setting, adhering to AHA guidance (3-5 years). Patients with moderate AS should be considered to remain under conservative follow-up (12-18 months). Follow-up for moderate AR, MR and MS can safely be adjusted towards the less conservative end of the AHA guidance (2 years).